Enhanced function of non-photoinhibited photosystem II complexes upon PSII photoinhibition - Gunell Sanna; Lempiäinen Tapio; Rintamäki Eevi; Aro Eva-Mari; Tikkanen Mikko (Elsevier BV, 2025)
Light induced photosystem (PS)II photoinhibition inactivates and irreversibly damages the reaction center protein(s) but the light harvesting complexes continue the collection of light energy. Here we addressed the consequences of such a situation on thylakoid light harvesting and electron transfer reactions. For this purpose, Arabidopsis thaliana leaves were subjected to investigation of the function and regulation of the photosynthetic machinery after a distinct portion of PSII centers had experienced photoinhibition in the presence and absence of Lincomycin (Lin), a commonly used agent to block the repair of damaged PSII centers. In the absence of Lin, photoinhibition increased the relative excitation of PSII and decreased NPQ, together enhancing the electron transfer from still functional PSII centers to PSI. In contrast, in the presence of Lin, PSII photoinhibition increased the relative excitation of PSI and led to strong oxidation of the electron transfer chain. We hypothesize that plants are able to minimize the detrimental effects of high-light illumination on PSII by modulating the energy and electron transfer, but lose such a capability if the repair cycle is arrested. It is further hypothesized that dynamic regulation of the LHCII system has a pivotal role in the control of excitation energy transfer upon PSII damage and repair cycle to maintain the photosynthesis safe and efficient.